(2019- تداعيات تذبذبات التضخم المستورد على التضخم المحلي في الجزائر خلال الفترة ( 1990: The repercussions of imported inflation fluctuations on domestic inflation in Algeria during the period (1990-2019) - دحماني فاطمة,; بوضياف سامية, (Journal of North African Economies, 2025)
Through this study, we aim to know the impact and type of relationship between domestic inflation, represented by the relative change in the consumer price index and imported inflation, represented by the relative change in import prices in addition to real GDP and real exchange rate, the monetary policy index represented by the monetary supply in its broad sense, and the financial policy represented by petroleum taxation, and in standard we used the method of self-regression with distributed slows (ARDL). Where the results of the tests of the root of the unit showed that all variables are stable at the first difference except the variable real exchange rate stable at the level, as showed that there is a structural shift in inflation and imported inflation 1997, 2017 respectively, and the results of the estimate showed the importance of the huge imported in explaining the rate of inflation in the long and short term, and also showed the existence of a direct relationship between domestic inflation and both the supply, the petroleum tax, and the opposite relationship between real output and the real exchange rate. In Algeria it arises as a result of internal and external factors.